2004
DOI: 10.1161/01.cir.0000130640.77501.79
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is an Important Determinant of Baseline Serum C-Reactive Protein Concentration in Monozygotic Twins, Independent of Genetic Influences

Abstract: Background-C-reactive protein (CRP) values predict atherothrombotic cardiovascular disease and type 2 diabetes mellitus. Associations between CRP and obesity, predominantly assessed anthropometrically, may partly explain these observations. Previous studies have been unable to control for genetic influences on CRP and obesity. The aim of this study was to examine the relationship between CRP and accurately measured body fat, lipids, apolipoproteins, blood pressure, and environmental and behavioral factors, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
122
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(133 citation statements)
references
References 65 publications
(76 reference statements)
9
122
1
1
Order By: Relevance
“…31 Some authors even proposed that elevated plasma IL-6 levels are a stronger predictor of cardiovascular mortality than CRP 63 and IL-6 seems to be the main circulating cytokine in systemic inflammation. 39,40 In accordance with previous studies, 16,47,64 we could demonstrate that plasma IL-6 levels were not influenced by age, BMI, sex, Family study CRP ++ + / / Vickers et al 13 Family study CRP ++ + + À Austin et al 15 Family study CRP + + + + Greenfield et al 43 Female twins CRP À + À / MacGregor et al 18 Female twins CRP ++ + / / Berger et al 44 Angiographic patients CRP / / + + Best et al 14 CHD patients CRP ++ / / / Latkovskis et al 45 CHD patients CRP / + À / Pantsulaia et al 41 Family study IL-6 + À + À Fishman et al 46 Healthy people IL-6 / / / / de Craen et al 42 Twin study IL-6 ++ / / / Posthuma et al 47 Twin study IL-6 ++ / À À Dupuis et al 48 Family study CRP/IL-6 +/+ / / / de Maat et al 16 Twin study CRP/IL-6 +/+ +/À À /+ / Abbreviations: BMI, body mass index; CHD, coronary heart disease; CRP, C-reactive protein; IL, interleukin.Owing to different statistical methods and partial lack of adjustment, we only reflect the opinion of the above-mentioned authors concerning the CRP/IL-6 heritability. Heritability: À: no heritability, +: slight heritability, ++: strong heritability, /: no statement.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…31 Some authors even proposed that elevated plasma IL-6 levels are a stronger predictor of cardiovascular mortality than CRP 63 and IL-6 seems to be the main circulating cytokine in systemic inflammation. 39,40 In accordance with previous studies, 16,47,64 we could demonstrate that plasma IL-6 levels were not influenced by age, BMI, sex, Family study CRP ++ + / / Vickers et al 13 Family study CRP ++ + + À Austin et al 15 Family study CRP + + + + Greenfield et al 43 Female twins CRP À + À / MacGregor et al 18 Female twins CRP ++ + / / Berger et al 44 Angiographic patients CRP / / + + Best et al 14 CHD patients CRP ++ / / / Latkovskis et al 45 CHD patients CRP / + À / Pantsulaia et al 41 Family study IL-6 + À + À Fishman et al 46 Healthy people IL-6 / / / / de Craen et al 42 Twin study IL-6 ++ / / / Posthuma et al 47 Twin study IL-6 ++ / À À Dupuis et al 48 Family study CRP/IL-6 +/+ / / / de Maat et al 16 Twin study CRP/IL-6 +/+ +/À À /+ / Abbreviations: BMI, body mass index; CHD, coronary heart disease; CRP, C-reactive protein; IL, interleukin.Owing to different statistical methods and partial lack of adjustment, we only reflect the opinion of the above-mentioned authors concerning the CRP/IL-6 heritability. Heritability: À: no heritability, +: slight heritability, ++: strong heritability, /: no statement.…”
supporting
confidence: 89%
“…24,39,[57][58][59][60] Khaodhiar et al 61 reported that in morbid obesity IL-6 may be secreted in an endocrine (systemic) manner in proportion to the expansion of fat mass particularly in the abdominal region with a corresponding increase in hepatic CRP production. Greenfield et al 43 examined the relationship between CRP and obesity in 194 healthy female twins and it seemed that obesity and adipose tissue are important determinants of baseline plasma CRP concentrations independent of genetic influences. Together with our findings of only a moderate genetic control of plasma CRP levels in corresponding with the opinion of Retterstol et al, 17 we suggested that a major part of the previously described CRP heritability was mediated by adipose tissue and the BMI.…”
mentioning
confidence: 99%
“…At the basic level, obesity is always due to greater energy intake than is expended, but the interaction of genetic and environmental factors that regulate both accumulation and distribution of body fat is complex. Recent studies of twins from our cohort, 2 and others, 3,4 have shown that total and central fat mass are responsible for most of the additional circulating inflammatory markers and cytokines that lead to increased heart disease. Determinants of fat accumulation include basal and sleeping metabolic rate, thermogenesis and the thermic effect of food, physical activity, efficiency of nutrient absorption by the gut and hormonal status, 5 which are all regulated differently depending on genetic make-up.…”
Section: Introductionmentioning
confidence: 59%
“…Those studies which adjusted for visceral adiposity, as measured by WHR or waist circumference, showed weaker associations than those that did not. Visceral adipose tissue, compared with subcutaneous fat, is known to produce more pro-inflammatory cytokines [37] and is associated with CRP levels [38], suggesting that visceral adiposity could be an additional important confounding factor that was not considered in all studies.…”
Section: Discussionmentioning
confidence: 99%